Absence of the RING domain in MID1 results in patterning defects in the developing human brain - Frank, Sarah; Gabassi, Elisa; Käseberg, Stephan; Bertin, Marco; Zografidou, Lea; Pfeiffer, Daniela; Brennenstuhl, Heiko; Falk, Sven; Karow, Marisa; Schweiger, Susann (Life science alliance, 2024)
The X-linked form of Opitz BBB/G syndrome (OS) is a monogenic disorder in which symptoms are established early during embryonic development. OS is caused by pathogenic variants in the X-linked gene MID1. Disease-associated variants are distributed across the entire gene locus, except for the N-terminal really interesting new gene (RING) domain that encompasses the E3 ubiquitin ligase activity. By using genome-edited human induced pluripotent stem cell lines, we here show that absence of isoforms containing the RING domain of MID1 causes severe patterning defects in human brain organoids. We observed a prominent neurogenic deficit with a reduction in neural tissue and a concomitant increase in choroid plexus-like structures. Transcriptome analyses revealed a deregulation of patterning pathways very early on, even preceding neural induction. Notably, the observed phenotypes starkly contrast with those observed in MID1 full-knockout organoids, indicating the presence of a distinct mechanism that underlies the patterning defects. The severity and early onset of these phenotypes could potentially account for the absence of patients carrying pathogenic variants in exon 1 of the MID1 gene coding for the N-terminal RING domain.
Online veröffentlicht: 18. Januar 2024
Gesehen am 11.06.2024